HUBUNGAN INTENSITAS NYERI DISMENORE DENGAN AKTIVITAS BELAJAR PADA REMAJA PUTRI USIA 15-18 TAHUN DI SMAN 1 BANGUNTAPAN YOGYAKARTA - Sanday, Septi Della; Kusumasari, Viantika; Sari, Dian Nur Adkhana (Universitas Ahmad Dahlan, 2019)
Dysmenorrhea is one of the menstrual problems experienced by teenage girls. According to WHO, the incidence of dysmenorrhea throughout the world estimated prevalence of 16.8% -81%. Dysmenorrhea pain felt by a teenage girl during menstruation can affect the daily activities, including in learning activities at school. The purpose of this study was to determine the relationship of dysmenorrhea with learning activities in a teenage girl aged 15-18 years at Public High School 1 Banguntapan, Yogyakarta. This study used a cross-sectional design. The population was teenage girl class X-XI at Public High School 1 Banguntapan, Yogyakarta, totalling 133 people. Samples amounted to 80 people. The sampling technique was purposive sampling. The research instrument used was NRS and learning activity questionnaire. Data analysis by Kendall tau. The results of this study showed that 42.5% of respondents experienced mild dysmenorrhea, and 57.5% experienced severe dysmenorrhea. Learning activities felt disturbed when dysmenorrhea was 88.8% of respondents, quite disturbed by 7.5%, and 3.8% felt undisturbed. The results of the Kendall analysis or the results show Ï = 0,000 (Ï <0.05). There is a relationship between dysmenorrhea with learning activities in a teenage girl aged 15-18 years at Public High School 1 Banguntapan, Yogyakarta.